Public risk management: managing risk in public institutions - Young, Peter C. (Henry Stewart Talks, 2012)
Publicness and public risks: the bigger picture, What is risk?, Public risk management: a brief history, Motives for current risk management practices, Enterprise risk management (ERM) the ISO 31000 framework, Establishing the ERM context, Risk assessment, Risk treatment, Monitoring and reviewing, Communication and consultation, ERM implementation: early evidence, Implementation: issues and obstacles, Summary